2022
DOI: 10.33188/vetheder.908566
|View full text |Cite
|
Sign up to set email alerts
|

Kuluçka sonrası farklı dönemlerde broyler ileumdaki mast hücrelerinin sayısı ve heterojenitesi

Abstract: Mast cells are located near surfaces that contact the external environment, such as the skin, respiratory, and digestive systems. The number of mast cells in tissues can vary depending on the location and immunological status of the host. This study aimed to determine the number and heterogeneity of mast cells in the broiler ileum during the post-hatching period. The number and heterogeneity of mast cells were studied in the ileum tissue of 0-, 7-, 21-and 42-day old broilers. Mast cells were stained metacromas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It has been suggested that there may be a colour change from blue to red in the staining properties of maturation of MCs with the alcian blue‐safranin sequence (Combs et al., 1965). A study on age‐related MC heterogeneity in the ileum has shown that AB (+) MCs were observed in all age groups starting at age 0, whereas SO (+) MCs were found beginning on the 7th day (Ertuğrul, 2022). In studies conducted to determine MC subtype in the tongue (Karaca & Yörük, 2004), it was reported that blue‐stained AB (+) and pink‐red‐stained SO (+) MCs were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that there may be a colour change from blue to red in the staining properties of maturation of MCs with the alcian blue‐safranin sequence (Combs et al., 1965). A study on age‐related MC heterogeneity in the ileum has shown that AB (+) MCs were observed in all age groups starting at age 0, whereas SO (+) MCs were found beginning on the 7th day (Ertuğrul, 2022). In studies conducted to determine MC subtype in the tongue (Karaca & Yörük, 2004), it was reported that blue‐stained AB (+) and pink‐red‐stained SO (+) MCs were observed.…”
Section: Discussionmentioning
confidence: 99%
“…MCs were observed in all age groups starting at age 0, whereas SO (+) MCs were found beginning on the 7th day (Ertuğrul, 2022). In studies conducted to determine MC subtype in the tongue (Karaca & Yörük, 2004), it was reported that blue-stained AB (+) and pinkred-stained SO (+) MCs were observed.…”
Section: Mast Cell Subtypes Mean ± Semmentioning
confidence: 93%